Principles of minimum wage policy: economics, institutions and recommendations - Herr, Hansjörg; Kazandziska, Milka (Geneva, 2011)
"On a macroeconomic level the main result is: Increases in minimum wages do not have big systematic employment effects, positive or negative. Inflationary pressures from minimum wages are usually small and tolerable. One very positive effect of minimum wages is that they change the wage structure in such a way that a more equal income distribution is reached. Minimum wage policy thus contributes to poverty reduction. To illustrate this: 12.5 per cent of the employees in Brazil receive the minimum wage and it has been found that the aggressive policy in Brazil during the past 8 years has had a strong effect on the compression of the wage structure (Lemos 2007). In some cases we can observe that minimum wages have even had a positive employment effect. The argument is based on the fact that low-wage earners have a higher propensity to consume than richer households and thus higher minimum wages increase aggregate demand and output. Furthermore, taking into consideration that women have a large share in the low-wage sector increasing minimum wages also has a positive gender equality effect. In this paper, on the basis of the theoretical model and case studies we have used, broad principles of minimum wage policy covering a large range of dimensions have evolved. We do not claim to have found the philosopher’s stone. This paper is meant as a contribution to the ongoing debate about minimum wage policy from a union perspective."